Hydration, Hygiene, and Health: Understanding Urinary Tract Infections Awareness in Female University Students - Md Faiazul Haque Lamem; Muaj Ibne Sahid; S Sadia; Tabassum Islam (Utan Kayu Publishing, 2026)
Urinary tract infections (UTIs) are common among women and pose significant public health challenges, yet data on knowledge, behaviors, and risk factors among female university students in Bangladesh remain limited. This study assessed UTI prevalence, awareness, and related practices among 112 female pharmacy students at R. P. Shaha University. Participants were primarily aged 21–23 years (56.7%), unmarried (91.1%), and urban residents (88.4%). About 32.1% reported a prior UTI, and nearly half (46.4%) consumed 2–3 liters of water daily. While 69.6% correctly identified bacteria as the leading cause, only 37.5% recognized that UTIs can affect multiple urinary tract sites, and 58.3% correctly noted that skin rash is not a typical symptom. Risk behaviors were prevalent, with 81.3% carrying water bottles, 40.2% wearing tight clothing 3–5 hours weekly, 45.5% occasionally delaying urination, and 39.3% consistently consuming fluids before bedtime. Comfort in discussing UTIs with healthcare providers varied, with 32.1% least comfortable and 25.9% most comfortable. These findings reveal substantial knowledge–practice gaps and underscore the need for targeted educational interventions and health promotion strategies to improve UTI prevention and awareness among future healthcare professionals.